The association between childhood maltreatment experiences and the onset of maltreatment perpetration in young adulthood controlling for proximal and distal risk factors. (August 2015) - Ben-David, Vered; Jonson-Reid, Melissa; Drake, Brett; Kohl, Patricia L.
Abstract: The evidence for association between child maltreatment victimization and later maltreatment perpetration is both scant and mixed. The objective of the present study was to assess the association between childhood maltreatment experiences and later perpetration of maltreatment in young adulthood controlling for proximal young adult functioning, prior youth risk behaviors, and childhood poverty. The study included 6, 935 low-income children with ( n = 4, 470) or without ( n = 2, 465) maltreatment reports prior to age 18 followed from ages 1.5 through 11 years through early adulthood (ages 18–26). Administrative data from multiple regional and statewide agencies captured reports of maltreatment, family poverty and characteristics, system contact for health, behavioral risks and mental health in adolescence, and concurrent adult functioning (crime, mental health and poverty). After controlling for proximal adult functioning, repeated instances of neglect or mixed type maltreatment remained associated with young adult perpetration. Females and subjects with adolescent history of runaway, violent behaviors or non-violent delinquency also had higher risk. Greater caregiver education remained associated with reduced risk. The study concludes that prevention of recurrent neglect and mixed forms of maltreatment may reduce risk of maltreatment for future generations. Intervening to increase parental education and decrease adolescent risk behaviors may offer additional benefit.